Crude versus case-mix-adjusted control charts for safety monitoring in thyroid surgery. Issue 6 (8th April 2010) - Duclos, Antoine; Voirin, Nicolas; Touzet, Sandrine; Soardo, Pietro; Schott, Anne-Marie; Colin, Cyrille; Peix, Jean-Louis; Lifante, Jean-Christophe
Abstract : Introduction: Patient-safety monitoring based on health-outcome indicators can lead to misinterpretation of changes in case mix. This study aimed to compare the detection of indicator variations between crude and case-mix-adjusted control charts using data from thyroid surgeries. Methods: The study population included each patient who underwent thyroid surgery in a teaching hospital from January 2006 to May 2008. Patient safety was monitored according to two indicators, which are immediately recognisable postoperative complications: recurrent laryngeal nerve palsy and hypocalcaemia. Each indicator was plotted monthly on a p-control chart using exact limits. The weighted κ statistic was calculated to measure the agreement between crude and case-mix-adjusted control charts. Results: We evaluated the outcomes of 1405 thyroidectomies. The overall proportions of immediate recurrent laryngeal nerve palsy and hypocalcaemia were 7.4% and 20.5%, respectively. The proportion of agreement in the detection of indicator variations between the crude and case-mix-adjusted p-charts was 95% (95% CI 85% to 99%). The strength of the agreement was κ=0.76 (95% CI 0.54 to 0.98). The single special cause of variation that occurred was only detected by the case-mix-adjusted p-chart. Conclusions: There was good agreement in the detection of indicator variations between crude and case-mix-adjusted p-charts. The joint use of crude and adjusted charts seems to be a reasonable approach to increase the accuracy of interpretation of variations in outcome indicators.